(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2017)
Those opposed to the social security reform proposals have focused their criticism on the introduction of a minimum retirement age for men and women. With the aim of broadening the debate and strengthening the currents that denounce the worsening situation of the working class, we have focused our analysis on the proposals to increase the contribution time, highlighting its impact on the main types of retirement under the General Social Security System (RGPS). From this point of view, we intend to shed light on the violence and depth of the proposed changes, which, if approved, could lead to the exclusion of the majority of workers from the already precarious scope of social security protection in Brazil.